Aplikasi Android Pengelolaan Akuarium dengan Menggunakan Arduino - Fendy Putra Wijaya Kusuma; Henry Novianus Palit; Handry Khoswanto (Jurnal Infra, 2017)
As we know technology is increasing. Many areas of life can be assisted and facilitated by the existence of the technology. Moreover, the use of the internet is increasing rapidly. However, the internet can also be used to help the small things in life. Ease of access of technology also triggered an ever increasing use of the internet. The use of smartphones is also growing in the    communities. Therefore, the use of smartphones and the internet to facilitate daily life is absolutely right. One of the problems that needs tp be solved is related to Aquarium. There are problems in managingf the Aquarium. The owners have complained that hard to maintance the aquarium. Especially when they leave the Aquarium for a long period of time. Certainly the Aquarium should still be treated each day. The most routine maintenance carried out covering the feeding and temperature settings. In solving the Aquarium, the author uses the arduino. The device is a microcontroller that can aid in the control of another device. The arduino device connected to the internet via wifi as intermediary. Furthermore, the arduino will be connected to the server. The connection to the server can connect the arduino with the database. The specified database can be modified using the android device, users can perform device settings the arduino using a smartphone. The result of this research is a system based on Arduino, Android technology and MySQL server. This allows the system to connect to each other through the internet network. The system consists of 3 main sections. The first part is a server as an intermediary between two other parts. The second part is an arduino as a physical device. The last part is the application of phonegap at android.